Satire Expressions in Animal Farm Novel by George Orwel : A Semantic Study - Anisa Melia Br Kemit; Hendar Hendar (Universitas Cokroaminoto Palopo, 2022)
The purpose of this research is to identify types of satire expressions and determine the purpose of satire in the Animal Farm novel containing criticism. The method used in this study is the descriptive analysis method, which means collecting the data, then processing and analyzing the data, and drawing a conclusion. The theory of satire used in this study is based on Holbert (2011) and Keraf (2006: 143). There are some satire expressions and types of satire found in 46 research data, namely: Juvenalian satire: Sarcasm 13 (28,26%); Irony 22 (47,83%), and Parody 11 (23.91%). The type of satire that is most commonly found in Animal Farm novel is Juvenalian satire, while the most common satire element is irony, which is 22 data. The purpose of the satire expressions in the Animal Farm novel is to criticize government policies. The government's policies are inhumane because the people are forced to achieve their goals, and the satire expressions in this novel also show how the government gains its power using cunning means.